Why should multiple dehiscences of the otic capsule be considered before surgically treating patients with superior semicircular canal dehiscence? A radiological monocentric review and a case series - Ionescu, Eugen C.; Reynard, Pierre; Damien, Maxime; Ltaief-Boudrigua, Aicha; Hermann, Ruben; Gianoli, Gerard J.; Thai-Van, Hung (Frontiers in Neurology, 2023)
The purpose of this review is to draw attention to the multiple ipsilateral otic capsule dehiscences, which may be the cause of therapeutic failure in operated patients. A series of six severely disabled patients with symptoms and signs consistent with a superior semicircular canal dehiscence diagnosis, confirmed by high-resolution CT scan is presented here. Five of the patients underwent surgery, and in 4 of the cases the postoperative results were poor and/or disappointing. Medical ethics teaches us that we must learn when things go wrong, especially when the medical staff has confidence in the accuracy of the proposed therapeutic techniques. Consequently, we reviewed the radiological records of symptomatic and asymptomatic patients diagnosed or referred to our center for confirmation over the past 5 years, to determine the incidence of multiple otic capsule dehiscence in this population. Multiple localizations of suspected otic capsule dehiscence in an ipsilateral ear does not appear to be rare and was found in 29 of 157 patients (18.47%) in our retrospective review using by high-resolution thin-sliced CT scans. The decision to perform surgery for a documented symptomatic superior semicircular canal dehiscence should be made with caution, only after ruling out concomitant lesser-known variants of otic capsule dehiscence in the ipsilateral ear.